Analisis Pasal 116 Undang-Undang Nomor 51 Tahun 2009 Tentang Perubahan Kedua Atas Undang-Undang Nomor 5 Tahun 1986 Tentang Peradilan Tata Usaha Negara Dari Perspektif Teori Perundang-undangan - Dola Riza (Normative Jurnal Ilmiah Hukum, 2025)
Article 116 of the State Administrative Court Law regulates the implementation of decisions of the State Administrative Court. In the event of a delay in the implementation (execution) of a court decision, in procedural law the State Administrative Court acting as the executor is the relevant state administrative agency or official. The implementation of decisions based on the legal awareness of state administrative officials results in many State Administrative Court decisions being disobeyed or not implemented by state administrative officials which can cause material and immaterial losses for the plaintiff. The formulation of the problem in this scientific work is how is the analysis of article 116 of law number 51 of 2009 concerning the second amendment to law number 5 of 1986 concerning state administrative justice from the perspective of statutory theory? The method used is normative research. The result of the discussion is that Article 116 Paragraph (3), Paragraph (4) and Paragraph (6) of the State Administrative Court Law does not expressly state a time limit for State Administrative Bodies or Officials to provide a decision (beschikking) in implementing the decision of the State Administrative Court.